Diversion as Protection of the Rights of Children in Conflict with Law - Rasdi, Rasdi (Law Research Review Quarterly, 2015)
The purpose of this research is to find out the type of legal products used by the Rembang Resort Police regarding the application of diversion in the settlement of cases of children in conflict with the law. In addition, also to know the diversion model or form applied by the Rembang Resort Police, so that it can be used as a means of resolving the cases of children in conflict with the law to achieve welfare, and to find out the obstacles and solutions.